Implications of the Inability of Listeria monocytogenes EGD-e To Grow Anaerobically Due to a Deletion in the Class III NrdD Ribonucleotide Reductase for Its Use as a Model Laboratory Strain - Ofer, Amos (American Society for Microbiology, 2011)
Listeria monocytogenes is a Gram-positive facultative intracellular bacterium that causes life-threatening diseases in humans. It grows and survives in environments of low oxygen tension and under conditions of strict anaerobiosis. Oxygen-limiting conditions may be an important factor in determining its pathogenicity. L. monocytogenes serovar 1/2a strain EGD-e has been employed intensively to elucidate the mechanisms of intracellular multiplication and virulence. Listeria possesses genes encoding class I aerobic and class III anaerobic ribonucleotide reductases (RNRs). The class III RNR consists of a catalytic subunit NrdD and an activase NrdG. Surprisingly, L. monocytogenes EGD-e, but not other L. monocytogenes strains or other listerial species, is unable to grow under strict anaerobic conditions. Inspection of listerial NrdD amino acid sequences revealed a six-amino acid deletion in the C-terminal portion of the EGD-e protein, next to the essential glycyl radical domain. Nevertheless, L. monocytogenes EGD-e can grow under microaerophilic conditions due to the recruitment of residual class Ia RNR activity. A three-dimensional (3D) model based on the structure of bacteriophage T4 NrdD identified the location of the deletion, which appears in a highly conserved part of the NrdD RNR structure, in the α/β barrel domain near the glycyl radical domain. The deleted KITPFE region is essential either for interactions with the NrdG activase or, indirectly, for the stability of the glycyl radical loop. Given that L. monocytogenes EGD-e lacks a functional anaerobic RNR, the present findings are relevant to the interpretation of studies of pathogenesis with this strain specifically, in particular under conditions of low oxygen tension.